Nutritional value and quality of quick-frozen fruits and berries using cryoprotectants - Kaminska (Halapsina), Svitlana (My University, 2023)
Fruits and berries (both cultivated and wild) serve as rich sources of vitamins, minerals, organic acids, macronutrients, and more. Their value as medicinal and food raw materials is determined by a complex of biologically active substances, including their qualitative and quantitative composition, the synergy of their actions, and a high degree of assimilation by living organisms. A significant portion of these biologically active substances possesses immunomodulatory, adaptogenic, anti atherosclerotic, hypotensive, and antioxidant properties.
Keywords: кафедра технології оздоровчих продуктів; dietary value; freezing fruit and berry; cryoprotectants; vitamin C; nutrients; organoleptic characteristics; дієтична цінність; заморожування фруктів і ягід; кріопротектори; вітамін С; поживні речовини; органолептичні показники